A Comparative Analysis of Nutritional Status Among Children in Rural and Urban Schools: A Cross-Sectional Study - Shastri, Shreya; George, Blessy; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice)
Background: Malnutrition, a major public health issue in developing countries, affects children’s growth and development, with varying incidence and prevalence between rural and urban populations. This study aims to assess and compare dietary habits and anthropometric indices among school-aged children (6-12 years) in urban and rural areas. Objectives: The primary objective is to assess and compare the nutritional status of children in rural and urban settings. Additionally, the study aims to estimate the prevalence of malnutrition through anthropometric indicators and enhance awareness among parents and children using PILs. Materials and Methods: This community-based, cross-sectional comparative study was conducted in rural and urban areas of Bengaluru with a sample size of 800. Anthropometric measurements, such as weight, height, midarm circumference, and age, were collected to assess underweight, wasting, stunting, and overweight prevalence. Results: In urban areas, children aged 8-9 years show the highest underweight (20%), stunting (17%), and wasting (16.25%), with the lowest rates in 12-year-olds (3%). In rural areas, underweight peaks in 10-11-year-olds (20.25%), stunting in 6-7-year-olds (10.25%), and wasting in the 10-11 group (15.5%). Discussion: Urban children show a sharp decline in underweight and stunting by age 12, while rural children experience persistent underweight and stable stunting. Wasting is generally higher in rural children, especially in older age groups, whereas urban children exhibit a notable decrease by age 12. Conclusion: Malnutrition affects both areas, but rural children have higher and more persistent rates, particularly in older groups, indicating the need for targeted nutritional interventions in rural settings.
Keywords: Anthropometric Measurements; Malnutrition; Underweight; Stunting